Comparison of mechanical properties of Sheep Hydroxyapatite (SHA) and Commercial Synthetic Hydroxyapatite (CSHA)-MgO composites - (:unkn) unknown (Trans Tech Publications Ltd, 2012)
In this study, microstructures and mechanical properties of sheep hydroxyapatite (SHA) and commercial synthetic hydroxyapatite (CSHA)-MgO composites were investigated. The production of hydroxyapatite (HA) from natural sources is preferred due to economical and time saving reasons. The goal of development of SHA and CSHA based MgO composites is to improve mechanical properties of HA. SHA and CSHA composites were prepared with the addition of different amounts of MgO and sintered at the temperature range of 1000-1300 °C. The physical and mechanical properties were determined by measuring density, compression strength and Vickers microhardness (HV). Structural characterization was carried out with X-ray diffraction (XRD) and scanning electron microscopy (SEM) studies. In all composites, mean density values and mechanical properties increased with increasing sintering temperature. The increase of MgO content in SHA-MgO composites showed better mechanical properties in contrast to CSHA-MgO composites. Although the highest hardness and compression strength values were obtained at the SHA-10wt% MgO composite sintered at 1300°C, higher hardness and compression strength values were achieved with 5 wt% MgO addition at the CSHA-MgO composites when compared to SHA-MgO composites sintered between 1000-1200°C. © (2012) Trans Tech Publications.
Keywords: Magnesium oxide; Mechanical properties; Sheep hydroxyapatite; Synthetic hydroxyapatite